Gingival health status in individuals using different types of toothpaste. (January 2019) - Pedersen, A.M.L.; Darwish, M.; Nicholson, J.; Edwards, M.I.; Gupta, A.K.; Belstrøm, D.
Abstract: Objectives: To examine the relationship between the medium term use (>1 year) of a toothpaste containing natural enzymes and proteins (Zendium™) upon gingival index, plaque index and bleeding index compared to medium term use of toothpastes without antimicrobial/antiinflammatory ingredients. Methods: A total of 305 participants eligible for inclusion were grouped according to their toothpaste use and matched with regard to gender and age (18–30, 31–55 and 56+ years of age). A total of 161 persons were using a toothpaste which contained enzymes and proteins (Zendium™, test group), and 144 persons were using a toothpaste without these ingredients (control group). The amount of dental plaque and the gingival condition were assessed at six sites of each tooth using the modified gingival index (MGI), plaque index (Modified Quigley and Hein plaque index, PI), and bleeding index (BI). Mean values of MGI, PI and BI were compared using analysis of covariance. Results: The test group had significantly less gingival inflammation than the control group (adjusted mean scores (SD); 1.80 (0.65) vs. 2.27 (0.63), p < 0.0001), as well as lower levels of plaque (2.03 (0.33) vs. 2.12 (0.33), p = 0.0168) and gingival bleeding (0.74 (0.45) vs. 1.08 (0.45), p < 0.0001). Females had significantly less gingival inflammation ( p < 0.0001), plaque ( p = 0.0005) and bleeding ( p = 0.0118) than males. Participants aged 18–30 years had significantly higher levels of inflammation and bleeding than the older age groups ( p < 0.001), and also higher plaque levels compared to participants aged 31–55 years ( p = 0.0069). Potential confounding factors including oral hygiene practices and consistency of dental visits did not differ between groups. Conclusions: Our findings indicate that medium term use of fluoride toothpaste containing enzymes and proteins (Zendium™) is associated with a better gingival health than the use of other types of fluoride toothpastes without antimicrobial active ingredients. Clinical significance: Medium term (> 1 year) use of toothpaste containing naturally occurring enzymes and proteins (Zendium™) in an unsupervised home setting is associated with better gingival health compared to the unsupervised use of other commercially available toothpastes without antimicrobial/antiinflammatory active ingredients.